Metode Hadis Sains dan Rasionalitas (Relevansi Klinis dan Teologis: Analisis Ma’anil Hadis tentang Hijamah (Bekam) dalam Perspektif Hematologi Modern): Metode Hadis Sains dan Rasionalitas (Relevansi Klinis dan Teologis: Analisis Ma’anil Hadis tentang Hijamah (Bekam) dalam Perspektif Hematologi Modern) - M. Sandri Ansari Ansari; Paidillah Rijani (Institut Agama Islam Darul Ulum Kandangan, 2025)
This article examines the Hadith on Hijamah (cupping therapy), which holds a central position within Thibbun Nabawi (Prophetic Medicine). Despite its historical and religious significance, hijamah is often marginalized by contemporary medical communities as pseudoscience or merely a cultural tradition. Conversely, many Muslims practice hijamah primarily on dogmatic grounds without critically examining its clinical mechanisms or biomedical implications. The objective of this study is to analyze the textual formulations of Hadith concerning hijamah and reconstruct their understanding through the lens of contemporary hematology in order to elucidate their clinical significance. This research employs a literature review approach, collecting data from diverse scholarly sources to ensure objective and systematic analysis. The Hadith examined are limited to those classified as ṣaḥīḥ or ḥasan. The scientific discussion further draws upon findings from modern medical textbooks and peer-reviewed journals that examine the physiological and clinical effects of hijamah. The study concludes that hijamah demonstrates significant clinical relevance as an evidence-based therapeutic intervention. The Prophetic Hadith on hijamah contains scientific indications that transcend its historical context, thereby challenging the perception of hijamah as merely a ta‘abbudī (purely ritualistic) practice. Instead, it should be understood as a rational (ta‘aqqulī) medical procedure grounded in empirical and physiological reasoning. Keywords : Cupping Therapy; Hijamah; Hadith; Prophetic Medicine (Thibbun Nabawi); Hematology.